Case of the Divergent Fallopian Tube: A Rare Cause of Intestinal Obstruction - Kohli, Mehul; Kansal, Shrey; Selvan, Muthamizh; Husain, Jafar (Lietuvos chirurgija, 2025)
Background. Intestinal obstruction is a common surgical emergency with diverse etiologies. While adhesions, hernias, and malignancies are frequently implicated, rare anatomical anomalies can occasionally be the cause. Methods. We report a case of a 66-year-old female who presented with complete obstipation for three days. Radiological evaluation revealed dilated bowel loops with a transition point at the distal ileum. Biochemical investigations were notable for metabolic acidosis. Results. Intraoperatively, an anomalous right-sided fallopian tube was identified obstructing the distal ileum, approximately 7 cm proximal to the ileocecal junction. The fallopian tube was resected (salpingectomy). Due to t hinning and impending perforation of the distal ileum, a diversion ileostomy with a distal mucous fistula was performed. Conclusion. This case highlights an unusual cause of small bowel obstruction and emphasizes the importance of considering rare anatomical anomalies in the differential diagnosis of intestinal obstruction.